2019
DOI: 10.1177/1934578x19876215
|View full text |Cite
|
Sign up to set email alerts
|

Gentiopicroside Reduces Pain, Pruritus, and Corticosteroid Addictive Dermatitis

Abstract: Corticosteroid addictive dermatitis (CAD) has rapidly emerged as a health problem which is difficult to cure. The dermatitis control is general with the tacrolimus, pimecrolimus, and antihistamines, and these synthetic drugs are likely to have some side effects, and how to use the nonirritating natural product to reduce the CAD has been rarely reported. Strong evidence indicates that gentiopicroside (GPS) has been reported to have anti-inflammation and anticancer properties. In the present study, we invented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Strong evidence from the previous literature showed that Compound 7 has strong anti‐inflammatory properties, reducing pain, pruritus, and CID repairment in animal models. The mechanistic pathways involved were found to induce TNF‐α, IL‐1β & P2X7R‐mediated inflammatory response via LKB1 and AMPK (Zhou et al, 2019).…”
Section: Natural Product Glycosides In Skin Disorder and Their Mechan...mentioning
confidence: 99%
“…Strong evidence from the previous literature showed that Compound 7 has strong anti‐inflammatory properties, reducing pain, pruritus, and CID repairment in animal models. The mechanistic pathways involved were found to induce TNF‐α, IL‐1β & P2X7R‐mediated inflammatory response via LKB1 and AMPK (Zhou et al, 2019).…”
Section: Natural Product Glycosides In Skin Disorder and Their Mechan...mentioning
confidence: 99%
“…Recently, it has been proven that gentiopicroside, the main secondary metabolites of G. asclepiadea underground parts, accelerates cutaneous wound healing by stimulating re-epithelialization, the development of granulation tissue, and enhanced collagen synthesis [ 13 ]. Gentiopicroside has also been reported to exhibit antipruritus, antipain, and reparative effects in corticosteroid addictive dermatitis [ 14 ]. Modern molecular modelling methods predicted that natural secoiridoids could be potent inhibitors of matrix metalloproteinases (the most potent among them were amarogentin and gentiopicroside), indicating their skin anti-photoaging potential [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The advantage of using TCM is related to its ability on affecting multiple signaling pathways and molecular targets cancerrelated, while causing few side effects. 13 Gentiopicroside isolated from Gentianella acuta, which has been shown to exert a wide spectrum of pharmacological activities, such as ameliorates diabetic nephropathy, 14 reducing Pain, Pruritus, and Corticosteroid Addictive Dermatitis, 15 as well as antidepressant-like effects, 16 and so on. Close attention has been paid to Gentiopicroside due to its potential role in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%